Spiritual and moral education - Oydinoy Nodirbek qizi Tolipova; Scientific advisor: M.M.Mirzakarimova (Science and Education, 2025)
The development of every advanced nation and people is closely linked to the moral values of individuals. This article discusses the concept of spiritual and moral education as one of the essential aspects of personality formation. It explores methods of instilling spiritual values and criteria in the younger generation and outlines effective approaches to moral education within the family, school, and society.